(untitled) (Czech Journal of International Relations, 1996)
Milan Hodža - Statesman and Politician. Materials from the Scientific Conference, Bratislava, September 15-17, 1992. Edited by PhDr. Miroslav Pekník, CSc. JL Revised and Expanded Edition. VEDA, Publishing House of the Slovak Academy of Sciences, Bratislava 1994, 88 pages, ISBN 80-224-0144-7.